Zoantharia (Anthozoa: Hexacorallia) abundance and associations with Porifera and Hydrozoa across a depth gradient on the west coast of Curaçao. Issue 8 (17th November 2018) - Reimer, James Davis; Wee, Hin Boo; García-Hernández, Jaaziel E.; Hoeksema, Bert W.
Abstract : Despite much research on zoantharians, little work has been done on the abundance of these animals in depths greater than 5 m. In this study, we examined the abundance of zoantharian species and their associated fauna at four depths (5, 10, 20, and 30 m) at multiple sites on the leeward west side of Curaçao in the southern Caribbean in order to provide baseline data. We aimed to quantify zoantharian-host associations in Curaçao to examine if the associations present vary according to different sites and across depths. Results showed that zooxanthellate Palythoa and Zoanthus were most common in shallow waters (5 m), although perhaps less common than observed 35–45 years ago, while sponge-associated species of Macrocnemina were commonly observed at greater depths. There was increasing zoantharian abundance and diversity with greater depth, and two major clusters of zoantharian assemblages in multi-dimensional scaling analyses, one cluster of shallow 5-m datasets, and the other of the large majority of 10-, 20-, and 30-m datasets, demonstrating that assemblages differed significantly by depth (5 m vs. 10, 20, 30 m). In contrast, no significant differences in zoantharian abundance or assemblage were seen across different sites. The data from this study establish a baseline of zoantharian assemblage data that can be compared with other regions and to datasets from Curaçao in the future, which will be of importance in tracking ecological shifts in the face of on-going climate change.